Examining Nepal’s Safe Motherhood and Reproductive Health Rights Act, 2018: A Legal Analysis - Neupane, Alaka (NPRC Journal of Multidisciplinary Research, 2025)
This paper provides a comprehensive doctrinal and analytical examination of Nepal’s Safe Motherhood and Reproductive Health Rights Act, 2018. By conducting a section-wise analysis of the Act’s provisions, the paper assesses how it recognizes, safeguards, and operationalizes reproductive health rights within Nepal’s constitutional framework and in alignment with international human rights standards. The paper highlights the Act’s groundbreaking provisions, such as the right to safe abortion, paid maternity leave, and protection against discrimination and coercion, while also identifying gaps and challenges in implementation. Key challenges include conflicting legal provisions (notably with the Labor Act, 2074), inadequate health infrastructure, and entrenched socio-cultural stigma that hinder the full realization of these rights. The paper concludes by emphasizing the Act’s progressive spirit and calls for harmonization of conflicting laws, investment in local health infrastructure, and robust awareness campaigns to transform this legislative promise into a lived reality for Nepali women.